Blockchain and IoT embedded sustainable virtual closed-loop supply chain in E-commerce towards the circular economy - Prajapati D.; Jauhar S.K.; Gunasekaran A.; Kamble S.S.; Pratap S. (My University, 2025)
Blockchain and the internet of things (IoT) have accelerated e-commerce growth and empowered online businesses to create value even in a globally competitive environment. The goal of this study is to develop a framework for the virtual closed-loop supply chain (VCLSC) that is based on novel blockchain and IoT technologies, as well as the concepts of sustainability and circular economy. This study integrates the normal and virtual supply chains into a single framework. To maximise the total expected revenue (TER) from the VCLSC, the costs of getting raw materials and parts, transporting them with a carbon emission tax, handling, processing, and making final products, refurbishing, recycling, and virtualization are all taken into account. These include running blockchain and IoT facilities, buying RFID tags, ensuring security, and storing data in blockchain in a way that cannot be changed. The above costs are captured in a single mixed-integer non-linear programming (MINLP) model. The main objective is to maximise the TER by minimising the cost of the VCLSC network. For the solution purposes, the global solver in LINGO 19 software package is used. The obtained results and performed sensitivity analysis are used to make some implications for business organisations and government administrators to create some important policies in favour of the environment, end-users, and the development of the organisation along with the nation. © 2022 Elsevier Ltd